TIDY UP BED SKILLS ASSESSMENT - Emay Mastiani; Lilis Suwandari; Eka Yuli Astuti (Journal of Disability, 2022)
Vocational assessment for students with intellectual disabilities  is designed to provide  information, readiness and diffulties in occupational functioning to performance a skill. The process of vocational assessment needed to be placed before the teacher compiling learning programs and the result of assessment will be used to determine curriculum modification need to be made to optimize students chances for success in the vocational programs. This study aims to determine the implementation of tidy up bed skills assessment that will be used in the preparation of vocational learning program for students with intellectual disabilities at high grade in Special School. The research method used in this research is a descriptive method with a qualitative approach. A variety of tehcniques are used to gathered information. Interviews, observations and documentation study are used to assess specific abilities related to a performance of skills. The steps taken in conducting the assessment are; preparation, implementation, analysis of assessment results, and communicating assessment results to whom it may concern. The instrumens of assessment are consists of aspects (1) tools knowledge, (2) the sequence steps of tidy up bed, (3) clear up tools, (4) maintenance process. The obstacle has been faced  is the teachers difficuties in analyzing and interpreting the results of the assessment. The results showed that some  students had basic abilities in simulating the work of tidy up bed , such as; prepare tools, tidy up bed, and maintaining clean bed and some others students didn’t shown the abilities to do  these steps. The results of the assessment explain the basic abilities of students and later  can be used as a reference to develop a learning program for tidy up bed skills